El esoterismo como propuesta identitaria en la novela "Regina 2 de octubre no se olvida" - Barajas-Garrido, Bernardo (University of Ottawa (Canada), 2003)
The present work intends to give a look inside the novel: Regina. 2 de octubre no se olvida, written in 1987 by the Mexican author Antonio Velasco Pina. The novel is an esoteric reinterpretation of the massacre that occurred in Mexico in 1968 when the Mexican government killed many students in a manifestation that was taking place at the Plaza de las Tres Culturas situated in Tlatelolco. The thesis is centered on the esoteric aspect of the novel as a new identity proposal for the Mexican society. To show this, our research includes the theory of construction of identity by opposites. We based this part on the studies done by Daniel Mato and Jorge Larrain. In the same line of thought the present research intends to show that identity is not a steady aspect of human life, but rather a continual construction and deconstruction of it. To show this, we are comparing the novel and what we believe is a new identity proposal with other works about Mexican identity such as the writings of authors like Octavio Paz, Jose Vasconcelos, Roger Bartra, Carlos Monsivais and others.
Keywords: Language, Modern.; Literature, Latin American.